Association between occupational and non-occupational risk to work-related musculoskeletal disorders among traffic police riders - Mohammad Yusof, Nur Athirah Diyana (2016)
Approximately 50% of the traffic police use a motorcycle as their main vehicle while on duty. These professional motorcycle riders are ride for many hours while on duty with the mean 5.64 hours per day which the exposure of vibration becomes critical since overexposure may cause discomfort, decrease their performance and even health risk including work-related musculoskeletal disorders (WMSDs). However, there have been no studies on vibration and WMSDs has been conducted among this group of workers in Malaysia. Thus, it is important that this research needs to be completed in order to identify the factors that can give health effects in developing WMSDs among traffic police riders. A cross-sectional study was done in Traffic Police Station in Kuala Lumpur and Johor Bahru on January until June 2015. One-hundred-and-thirty-seven riders participated in this study. A set of questionnaire which included Standardized Nordic Questionnaire was used. The Svantek 106 is a six-channel human vibration meter was also used to assess and measure the level of Whole Body Vibration (WBV) and Hand Arm Vibration (HAV). The one-year prevalence of WMSDs among the traffic police riders was 67.9%. The highest WMSDs symptom was reported at the neck (35.8%) and shoulder (35.8%). The mean WBV and HAV of frequency-weighted acceleration in eight hours, A(8) was 0.44 m/s2 and 2.25 m/s2 respectively. Meanwhile, the level of Vibration Dose Value (VDV) in WBV exposure was 13.85 m/s2. Multiple logistic regression analysis revealed that duration of riding traffic police motorcycle (OR= 0.175, 95% CI:0.052, 0.581), year of services as traffic police riders (OR=0.152, 95% CI: 0.040, 0.567), and HAV in A(8) (OR=3.053, 95% CI: 1.126, 8.280) were significant risk factors to one-year prevalence of WMSDs. As a conclusion, although the level of WBV and HAV did not exceed both Exposure Action Value (EAV) and Exposure Limit Value (ELV) in term of A(8), the VDV level in WBV was exceeded EAV. In addition, ninety-three of the traffic police riders reported WMSDs symptoms for the past 12 months. Duration of riding (OR= 0.175, 95% CI:0.052, 0.581), year of services as traffic police riders (OR=0.152, 95% CI: 0.040, 0.567) and HAV in A(8) (OR= 3.053, 95% CI: 1.126, 8.280) were found to be most important risk factors for WMSDs among traffic police rider.